Study of Probability of Microscopic Pore Formation in Post-Thaw Sperm Membranes - Butskyi, Kyrylo I.; Dyubko, Tatyana S.; Fedunyayeva, Irina A.; Tatarets, Anatoliy L.; Kopeika, Evgeniy F. (Problems of Cryobiology and Cryomedicine, 2015)
N/A